Legal Requirements for Public Procurement Electronic Platforms: The TrivPlat Project - Cunha, S. (2018)
Electronic public procurement (EPP) has been considered an important tool for promoting competition, simplifying procedures, and ensuring transparency in decision-making processes. In Portugal, EPP replaced paper-based pre-contractual procedures for communication and processing. Addressing this general issue, the authors designed and proposed the TrivPlat, a free access tool for monitoring, managing, and evaluating the electronic platforms of public procurement. This tool is even more relevant if we take into account that the current legal framework establishes the free choice of electronic platforms for contracting authorities and economic operators. This paper presents the TrivPlat project, reporting its development by now: the identification and characterization of legal requirements that electronic platforms for public procurement are complied to obey in Portugal. These requirements may be grouped into four types: general operating rules, functional requirements, technical requirements, and safety requirements. In addition, within the actual regulatory framework, they correspond to a new paradigm.